A porous tetraphenylethylene-based polymer for fast-response fluorescence sensing of Fe(III) ion and nitrobenzene. (February 2020) - Zheng, Yingting; Wang, Hailong; Jiang, Jianzhuang
Abstract: A fluorescent porous tetraphenylethylene-based organic polymer (PTOP ) was constructed by the reaction of 5, 5', 5'', 5‴-(ethene-1, 1, 2, 2-tetrayltetrakis(benzene-4, 1-diyl))tetrakis(pyrimidin-2-amine) and cyanuric chloride in the presence of potassium carbonate. CO2 sorption experiment at 195 K reveals the permanent porosity of PTOP with a Brunauer-Emmett-Teller surface area of 227 m 2  g −1 . In particular, the existence of rich secondary amines and pyrimidine nitrogen atoms surrounding the 1, 3, 5-triazine moieties in PTOP provides abundant chelating sites for metal ions, endowing a fast-response and sensitive fluorescence sensing Fe(III) with a low limit of detection of 4.5 μM. In addition, this polymer also shows an excellent sensing performance towards nitrobenzene with good selectivity and a low detection limit of 1.6 nM. Graphical abstract: A fluorescent porous tetraphenylethylene-based organic polymer (PTOP ) was constructed and capable of exhibiting a fast-response and sensitive fluorescence sensing both Fe(III) and nitrobenzene. Image 1 Highlights: A fluorescent porous tetraphenylethylene-based organic polymer (PTOP ) was constructed. CO2  sorption experiment reveals that the BET surface area of PTOP  is 227 m 2  g –1 . PTOP  endows a fast-response and sensitive fluorescence sensing Fe(III) and nitrobenzene with low LOD of 4.5 μM and 1.6 nM.